Energy monitoring in IoT-based ad hoc networks: An overview. (June 2019) - Al-Turjman, Fadi; Altrjman, Chadi; Din, Sadia; Paul, Anand
Abstract: Nowadays, utilities are being stressed for further gigantic energy production. Exponential growth of human population and energy consumers in mega cites is witnessed. And thus, energy conservation is becoming a major concern worldwide. As a result, energy-monitoring systems are evolving as the most effective solution towards optimizing the growing energy demands and consumptions. These systems can eliminate the waste in energy, reduce the current usage levels, and better utilize our resources. In this work, we overview and categorize existing energy-monitoring approaches in the literature. Enabling technologies including sensors and handheld devices are overviewed as well. We spot the light on practical aspects and performability issues. Furthermore, we investigate the impact and effectiveness of these monitoring systems under stress. Critical design factors, tuning parameters and real use cases are analyzed and compared in addition to categorizing the most common trends in this area. Finally, commonly observed patterns and statistics are concluded and reported.